PUBLIC POLICY AND ITS ROLE IN CONTEMPORARY CIRCUMSTANCES - Валерија Шаула (Годишњак Правног факултета у Бањалуци)
The paper deals with the issue of a public policy, predominantly as an instrument in the area of Private International Law, though it can be used in other fields of law. Describing the origin and a role of a public policy as a protecting mechanism in the process of application of foreign law, applicable under conflict of laws rules, in the process of recognition of foreign judgments and arbitral awards, as well as a mechanism for refusing to provide international legal assistance, the author contemplates about the role and place of this institute in contemporary world, when the differences between the national legal systems rarely can be seen as insurmountable obstacle for their application.